Different measures of HMGB1 location in cancer immunology - Gorgulho, Carolina Mendonca [UNESP]; Murthy, Pranav; Liotta, Lance; Espina, Virginia; Lotze, Michael T.; Galluzzi, L.; Rudqvist, N. P. (Elsevier B.V., 2019)
HMGB1 is the most abundant non-histone nuclear protein. It regulates transcriptional access to open areas of chromatin and limits release of DNA with apoptotic death, serving to both inhibit apoptosis and promote DNA repair. When HMGB1 is translocated to the cytosol with many types of cellular stress, it is a powerful inducer of autophagy. It can also be released by activated immune cells and damaged or dying cells into the extracellular space, where it acts as a damage associated molecular pattern (DAMP) molecule, contributing to the pathogenesis and progression of cancer. Here, the most common methodologies to not only measure HMGB1 but also to effectively determine its subcellular localization, which dictates many of HMGB1's different functions, are reviewed.